Battery electrode and manufacturing method thereof

By using the polymer obtained by copolymerizing α,β-ethylenically unsaturated carboxylic acid monomer and (meth)acrylamide monomer as the binder, the problem of poor adhesion of PTFE adhesive in the dry electrode process is solved, and the adhesion and electrochemical stability of the electrode are improved, especially in the silicon anode, and durability and electrochemical properties are enhanced.

CN119856287APending Publication Date: 2025-04-18SPECIALTY OPERATIONS FRANCE SAS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380064569.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-08
Filing Date
2023-09-04
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the existing dry electrode process, PTFE as an adhesive has a problem of poor adhesion, especially the electrochemical stability on the anode side is limited, and the silicon anode causes mechanical stress due to volume changes during the charge-discharge cycle, resulting in reduced capacity and failure of the electrochemical cell.

Method used

The polymer obtained by copolymerizing α,β-ethylenically unsaturated carboxylic acid monomer and (meth)acrylamide monomer is used as the binder, and combined with the electrode active material and the conductive agent by dry mixing to form a self-supported dry film and applied to the conductive substrate.

Benefits of technology

It improves the adhesion and electrochemical stability of the electrode, enhances the durability and electrochemical properties of the silicon anode, and extends the service life of the electrochemical cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005301655510000031
    Figure BDA0005301655510000031
  • Figure BDA0005301655510000032
    Figure BDA0005301655510000032
  • Figure BDA0005301655510000041
    Figure BDA0005301655510000041
Patent Text Reader

Abstract

The invention relates to an electrode powder composition, to a method for the production thereof and to the use thereof for producing electrochemical cell parts.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to prior applications

[0002] This application claims priority from European application number 22306333.0 filed on September 8, 2022, the entire contents of which are incorporated by reference into this application for all purposes. Technical Field

[0003] The invention relates to an electrode powder composition, a process for its preparation and its use for producing electrochemical cell components. Background Art

[0004] To date, electrodes of lithium secondary batteries have been mainly manufactured by a wet process including preparing a slurry in which an electrode active material, an additive, and a binder are dispersed in a solvent or an aqueous medium, and processing the slurry in such a manner as to form an electrode film.

[0005] Dry electrode processes have been developed to reduce the time-consuming and expensive drying procedures required by the above-mentioned wet processes.

[0006] Typical dry processes take advantage of the fibrillation properties of certain polymers to provide a matrix for embedded conductive materials. Some polymers in the fluoropolymer family, such as polytetrafluoroethylene (PTFE), are particularly inert and stable in common electrolyte solvents used in secondary batteries, even with organic solvents at high operating or storage temperatures. Therefore, the stability of electrodes made with PTFE can be higher than those made with other binders.

[0007] For example, a dry electrode preparation process may include combining a PTFE binder with an active electrode material in powder form, and calendaring to form an electrode film. However, although PTFE has good adhesion to electrode active materials, it has difficulty adhering to current collectors.

[0008] Another disadvantage of PTFE is related to its limited electrochemical stability on the anode side, which may lead to polymer degradation and result in lower coulombic efficiency when used as a binder for the anode.

[0009] Furthermore, when the anode is made of silicon, one of the key obstacles to overcome is the significant volume changes that occur in the silicon active material as it absorbs (expands) and desorbs (contracts) lithium during charge-discharge cycles. These significant shrink-expansion cycles impose high mechanical stresses on the anode layer, leading to fractures and contact loss in the circuit, resulting in reduced capacity and eventual failure of the electrochemical cell.

[0010] To overcome the specific challenges associated with silicon, one approach is to create a self-healing mechanism in the binder matrix by incorporating weak bonding interactions that enable a degree of reversibility, where these unstable bonds can be broken under stress but reform upon relaxation without irreparable damage to the active material particles. Unfortunately, PTFE cannot interact tightly with the active material through such bonding interactions and is not a good candidate binder for silicon-rich anodes.

[0011] Many approaches are being pursued to develop next generation binders to accommodate silicon anodes.

[0012] A variety of polycarboxylate binders and derivatives are being pursued, including polyacrylic acid, polyamic acid, polyacrylamide, and other hydrogen-bonding structures.

[0013] The Applicant has surprisingly found that certain polymers obtained by copolymerization of at least one monomer carrying a carboxyl group and at least one monomer carrying an acrylamide group can be used in dry electrode preparation processes, in particular for preparing silicon-rich anodes, thereby providing electrodes by a very efficient process. Summary of the invention

[0014] In one aspect, therefore, the present invention provides a method for producing an electrode of an electrochemical cell [electrode (E)], said method comprising, preferably consisting of, the following steps:

[0015] -i) providing a polymer (P) comprising:

[0016] (A) repeating units derived from at least one α,β-ethylenically unsaturated carboxylic acid monomer [monomer (AA)]; and

[0017] (B) repeating units derived from at least one (meth)acrylamide monomer [monomer (AM)] having formula (I)

[0018]

[0019] in

[0020] R 5 represents a hydrogen atom or a methyl group, R 6 and R 7 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, R 8 and R 9 , which are the same as or different from each other, may be selected from the group consisting of a hydrogen atom, a straight or branched chain alkyl group having 1 to 6 carbon atoms, a carboxyl group, and an amide group;

[0021] (C) optionally, a repeating unit derived from at least one monomer (M) selected from the group consisting of monomer (M1) and monomer (M2),

[0022] in

[0023] - Monomer (M1) is an ethylenically unsaturated monomer carrying an unsaturated heterocyclic group having at least one nitrogen atom, said monomer (M1) having the following formula (II):

[0024]

[0025] in:

[0026] R 1 is H or alkyl, wherein the alkyl is preferably methyl;

[0027] R 2 is H or alkyl;

[0028] R 3 and R 4 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms;

[0029] A is a connecting bond selected from the group consisting of:

[0030] - single covalent bonds; and

[0031] - spacer groups;

[0032] wherein X, Y and Z are independently selected from carbon atoms or nitrogen atoms;

[0033] wherein a, b and c are independently selected from integers 1 to 2;

[0034] Each dashed line represents an optional double bond;

[0035] - a monomer (M2), which is different from monomer (AA) and monomer (AM), said monomer (M2) having the following formula (III):

[0036]

[0037] in:

[0038] R i Selected from the group consisting of: H, -COOH, -CH2COOH or alkyl, wherein the alkyl is preferably methyl;

[0039] R ii and R iii , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, or may be a -COOH group;

[0040] B is a linker selected from the group consisting of: a -C(O)-O- group and a -C(O)-NH- group;

[0041] R x A straight or branched C3-C4- 20 Hydrocarbon chain part: ether (-O-), heterocyclic group, sulfonic acid group (-SO3H), sulfonic acid salt (-SO3Cat), phosphonic acid group (-PO3H2), phosphonic acid salt (-PO3Cat2), phosphoric acid group (-OPO3H2), and phosphoric acid salt (-OPO3Cat2), wherein Cat is a monovalent cation, which is preferably selected from alkali metal cations, more preferably selected from Na + , K + and Li + ;

[0042] -ii) dry mixing at least one electrode active material (AM), the polymer (P) provided in step i) as defined above, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode forming composition [composition (C)];

[0043] -iii) feeding the composition (C) obtained in step ii) to a compactor to form a self-supporting dry film; and

[0044] -iv) applying the dry film to a conductive substrate to form the electrode.

[0045] In another aspect, the present invention provides an electrode (E) for a secondary battery obtainable by the method as defined above.

[0046] The polymer (P) can be conveniently used as the sole binder or blended with PTFE and has high adhesion even at moderate processing temperatures (about 100°C).

[0047] In another aspect, therefore, the present invention provides a method for producing an electrode of an electrochemical cell [electrode (E1)], the method comprising:

[0048] - step I) combining polytetrafluoroethylene (PTFE) and a polymer (P) as defined above to provide a binder (B);

[0049] - step II) dry mixing at least one electrode active material (AM), a binder (B) as defined above, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode forming composition [composition (C1)];

[0050] - step III) feeding the composition (C1) obtained in step II) into a compactor to form a self-supporting dry film; and

[0051] - Step IV) applying the dry film to a conductive substrate to form the electrode.

[0052] In another aspect, the present invention provides an electrode (E1) for a secondary battery obtainable by the method as defined above.

[0053] In a further aspect, the present invention relates to an electrochemical device, such as a secondary battery or a capacitor, comprising at least one electrode (E) or electrode (E1) as defined above. DETAILED DESCRIPTION

[0054] In the context of the present invention, the term "weight percent" (wt%) indicates the content of a specific component in a mixture, calculated as the ratio between the weight of the component and the total weight of the mixture. When referring to repeating units derived from a certain monomer in a polymer / copolymer, the weight percent (wt%) indicates the ratio between the weight of repeating units of this monomer and the total weight of the polymer / copolymer. When referring to the total solid content of a liquid composition, the weight percent (wt%) indicates the ratio between the weights of all non-volatile components in the liquid.

[0055] As used herein, the terms "attach" and "adhere" indicate that two layers are permanently adhered to each other via their contacting surfaces.

[0056] The term "electrochemical device" is intended herein to mean an electrochemical cell / assembly comprising a positive electrode, a negative electrode and a liquid electrolyte, wherein a single-layer or multi-layer separator is in contact with at least one surface of one of the electrodes. Non-limiting examples of suitable electrochemical devices include notably secondary batteries, especially alkali metal or alkaline earth metal secondary batteries (such as lithium ion batteries, lead-acid batteries), and capacitors, especially lithium ion-based capacitors and double-layer capacitors (supercapacitors). Non-limiting examples of electrochemical cells include notably batteries (preferably secondary batteries), and double-layer capacitors.

[0057] For the purposes of the present invention, "secondary battery" is intended to mean a rechargeable battery. Non-limiting examples of secondary batteries notably include alkali metal or alkaline earth metal secondary batteries.

[0058] Polymer (P)

[0059] In step i) of the process of the present invention, a polymer (P) is provided, wherein the polymer (P) is obtainable by free radical copolymerization of a mixture of at least one α,β-ethylenically unsaturated carboxylic acid monomer (AA) and at least one (meth)acrylamide monomer [monomer (AM)] as defined above.

[0060] The at least one α,β-ethylenically unsaturated carboxylic acid monomer (AA) is preferably a compound having formula (IV):

[0061]

[0062] Where R a , R b and R c , which are the same as or different from each other, are independently selected from a hydrogen atom and a C1-C3 hydrocarbon group.

[0063] More preferably, monomer (AA) is a compound of formula (IV) as defined above, selected from the group consisting of acrylic acid, methacrylic acid, Sipomer BCEA (sold by Solvay), ethacrylic acid, crotonic acid, methyl (meth)acrylic acid, ethyl (meth)acrylic acid, propyl (meth)acrylic acid, isopropyl (meth)acrylic acid, n-butyl (meth)acrylic acid, 2-ethylhexyl (meth)acrylic acid, n-hexyl (meth)acrylic acid and n-octyl (meth)acrylic acid.

[0064] The (meth)acrylamide monomer [monomer (AM)] having formula (II) is preferably selected from the group consisting of (meth)acrylamide or N-substituted (meth)acrylamide, such as N-alkylacrylamide, N,N-dialkylacrylamide.

[0065] According to an embodiment of the present invention, the polymer (P) comprises at least one monomer (M1) which is an ethylenically unsaturated monomer as defined above carrying an unsaturated heterocyclic group having at least one nitrogen atom.

[0066] The "unsaturated heterocyclic group having at least one nitrogen atom" in the monomer (M1) having the formula (II) preferably includes a 5- to 6-membered aromatic ring group having at least one N in the ring, and such as:

[0067]

[0068] Where * indicates the connection point of the connection key A.

[0069] Linking bond A and residue R 2 Attachment to the heterocyclic group may be at any position (on a carbon atom or a nitrogen atom).

[0070] The monomer (M1) may be, for example:

[0071] - Vinylimidazole (VIm) having the formula (IIa):

[0072]

[0073] - 2-methyl-1-vinylimidazole having formula (IIb)

[0074]

[0075] - 1-vinyl-1,2,4-triazole having formula (IIc)

[0076]

[0077] - 2-vinylpyrazine having formula (IId)

[0078]

[0079] - 4-vinylpyridine having formula (IIe)

[0080]

[0081] - 2-vinylpyridine having formula (IIf)

[0082]

[0083] -Hydroxy-(meth)acrylate imidazole derivatives having formula (IIg)

[0084]

[0085] The divalent spacer group A in formula (II) can typically be a group -CO-NH-(CH2) n -、-CO-O-(CH2) n or -CO-O-(CH2) n -O-CO-, but any other covalently linked group is contemplated, such as that resulting from the reaction of a compound of formula (II-X):

[0086]

[0087] Where R 6 , R 8 and R 9 is as defined above,

[0088] With a compound having formula (II-Y):

[0089]

[0090] Where R 2 is as defined above, A 1 and A 2 Are two groups that react together to form a covalent bond.

[0091] For example, A2 It can be -(CH2) m -NH2 group, wherein m is 1 to 4, preferably 2 or 3. In this case, A 1 It may be, for example, a carboxylic acid, an acid chloride, an anhydride or an epoxide.

[0092] According to another variant, A 2 It can be -(CH2) m -OH group, wherein m is 1 to 4, preferably 2 or 3. In this case, A 1 It may be, for example, a carboxylic acid, an acid chloride, an anhydride or an ester.

[0093] According to this embodiment, polymer (P) is a polymer obtained by copolymerizing monomers (AA), (AM) and at least one monomer (M1), i.e., it has a structure obtained by such polymerization, but polymer (P) is not necessarily obtained by this method. As an alternative, polymer (P) can be obtained, for example, by the following method: first step copolymerizing monomers (AA), monomers (AM) and a compound having formula (II-X) to produce polymer (P0), and then second step post-grafting polymer (P0) by reacting with compound (II-Y).

[0094] When A in compound (II-Y) 2 Yes - (CH2) m When the -NH2 group is present, compound (II-X) may advantageously be selected from: additional acrylic or methacrylic acid, or esters thereof; maleic anhydride; vinylbenzyl chloride; glycidyl methacrylate; and (blocked) isocyanatoethyl methacrylate.

[0095] When A in compound (II-Y) 2 Yes - (CH2) m When there is an -OH group, compound (II-X) may advantageously be selected from acrylic acid, methacrylic acid, maleic anhydride, or their esters.

[0096] Furthermore, quaternization of all or part of the imidazole functions of the polymer (P) can take place, resulting from quaternization of all or part of the monomers and / or from post-quaternization of all or part of the imidazole functions of the polymer.

[0097] According to another embodiment of the present invention, the polymer (P) comprises at least one monomer (M2) having formula (III) as defined above.

[0098] The residue R of the monomer (M2) x The "heterocyclic group" in the formula (a) includes a saturated heterocyclic group of a compound having at least one nitrogen atom, such as imidazolidinone.

[0099] According to the first variant in which B in formula (III) is a -C(O)-O- group, monomer (M2) may for example be a compound having formula (IIIa)

[0100]

[0101] Compounds having formula (IIIb)

[0102]

[0103] Compounds having formula (IIIc)

[0104]

[0105] Wherein in formula (IIIa) to (IIc), R i , R ii and R iii As defined above, and n is an integer from 1 to 40.

[0106] According to the second variant in which B in formula (III) is a -C(O)-NH- group, monomer (M2) may for example be a compound of formula (IIId)

[0107]

[0108] or a compound having formula (IIIe)

[0109]

[0110] Wherein in formula (IIId) and (IIIe), R i , R ii and R iii As defined above.

[0111] According to this embodiment, polymer (P) is a polymer obtained by copolymerizing monomers (AA), (AM) and at least one monomer (M2), ie it has a structure obtained by such polymerization, but polymer (P) is not necessarily obtained by this method.

[0112] At least one polymer (P) may further comprise less than 10 % by mole of one or more additional monomers (M') selected from the group consisting of hydrophobic monomers and amphiphilic monomers, provided that the total amount of monomers (AA) and / or monomers (AM) relative to the total moles of repeating units of the polymer (P) is at least 60 % by mole.

[0113] In this embodiment, when additional monomers (M') are present in the polymer (P), the hydrophobic and / or amphiphilic monomers are selected from the group consisting of the following monoethylenically unsaturated monomers:

[0114] - alkyl esters of maleic anhydride and (meth)acrylic acid, such as monomethyl maleic anhydride, dimethyl maleic anhydride, monoethyl maleic anhydride, diethyl maleic anhydride, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate,

[0115] - hydroxyalkyl esters of maleic anhydride and (meth)acrylic acid, such as monohydroxyethyl maleic anhydride, dihydroxyethyl maleic anhydride, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate

[0116] - ethoxylates and propoxylates derived from maleic anhydride, such as poly(propylene oxide)-b-poly(ethylene oxide) maleic acid half- or diesters, alkyl-poly(ethylene oxide) maleic acid half- or diesters,

[0117] - ethoxylates and / or propoxylates derived from ethoxylation and / or propoxylation of hydroxyalkyl(meth)acrylic acids, such as poly(propylene oxide)-b-poly(ethylene oxide)-ethyl(meth)acrylate

[0118] - ethoxylates and / or propoxylates derived from (trans)esterification of (meth)acrylic acid and esters, such as poly(propylene oxide)-b-poly(ethylene oxide) (meth)acrylate and alkyl-poly(ethylene oxide) (meth)acrylate

[0119] - vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, 2-ethylhexyl vinyl ether, vinyl cyclohexyl ether, dodecyl vinyl ether, 2-(diethylamino)ethyl vinyl ether, 2-(di-n-butylamino)ethyl vinyl ether, allyl ethers such as methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, 2-ethylhexyl vinyl ether,

[0120] - vinyl esters, such as vinyl acetate or vinyl propionate; alkyl-substituted acrylamides, such as N-tert-butylacrylamide or N-methyl(meth)acrylamide.

[0121] Preferably, the additional monomers (M') present in the polymer (P) are selected from the group consisting of:

[0122] - Monoethyl maleate, diethyl maleate, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate

[0123] - Monohydroxyethyl maleate, dihydroxyethyl maleate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate

[0124] -Poly(propylene oxide)-b-poly(ethylene oxide) maleic acid half ester

[0125] -Poly(propylene oxide)-b-poly(ethylene oxide)-ethyl(meth)acrylate

[0126] -poly(propylene oxide)-b-poly(ethylene oxide) (meth)acrylate, alkyl-poly(ethylene oxide) (meth)acrylate

[0127] - Vinyl acetate, vinyl propionate.

[0128] The molar proportion of monomers (M') cannot exceed 10% by mole of the total moles of monomers (AA+AM+M+M') present in the polymer (P). Advantageously, the molar proportion of monomers (M') is lower than 5% by mole.

[0129] At least one polymer (P) may further comprise less than 1 % by mole of one or more additional crosslinking monomers (XL-M) comprising at least two ethylenic unsaturations.

[0130] In this embodiment where additional monomers (XL-M) are present in the polymer (P), the crosslinking monomers may be selected from N,N'-methylenebisacrylamide (MBA), N,N'-ethylenebisacrylamide, polyethylene glycol (PEG) diacrylates, triacrylates, divinyl ethers, typically trifunctional divinyl ethers such as tri(ethylene glycol) divinyl ether (TEGDE), N-diallylamine, N,N-diallyl-N-alkylamines, acid addition salts thereof and quaternization products thereof, the alkyl group used here being preferably (C1-C3)-alkyl; N,N-diallyl-N-methylamine and N,N-dimethylammonium compounds, for example chlorides and bromides; or alternatively, ethoxylated trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate (DiTMPTTA), divinylbenzene (DVB), ethoxylated or propoxylated bisphenol A diacrylate, dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), propoxylated di(meth)acrylates, butoxylated di(meth)acrylates, dimethylacrylamide, 1,4-butanediol dimethacrylate (BDDMA), 1,6-hexanediol dimethacrylate (HDDMA), 1,3-butanediol dimethacrylate (BGDMA), and derivatives thereof.

[0131] The molar proportion of monomers (XL-M) must not exceed 1% by mole of the total moles of monomers (AA+AM+M+M'+XL-M) present in the polymer (P) to avoid gel formation and viscosity increase. Advantageously, the molar proportion of monomers (M') is lower than 0.5% by mole.

[0132] According to said embodiment, the polymer (P) obtained by the polymerization further comprising monomers (XL-M) is at least partially crosslinked.

[0133] In a preferred embodiment of the present invention no further monomers (M') or (XL-M) are present in the polymer (P).

[0134] Typically, the polymer (P) is obtained by free radical copolymerization of a mixture of:

[0135] - at least one monomer (AA),

[0136] - at least one monomer (AM),

[0137] - optionally at least one monomer (M),

[0138] - optionally at least one monomer (M'), and,

[0139] - optionally at least one monomer (XL-M).

[0140] Any free radical source can be used. In particular, the free radicals can be generated spontaneously, for example by increasing the temperature, using suitable monomers, such as styrene. The free radicals can be generated by irradiation, in particular by UV irradiation, preferably in the presence of a suitable UV-sensitive initiator. Initiators or initiator systems of free radical or redox type can be used. The free radical source may or may not be water-soluble. It may be preferred to use a water-soluble initiator or an at least partially water-soluble initiator.

[0141] In general, the greater the amount of free radicals, the easier it is to initiate polymerization (promote polymerization), but the lower the molar mass of the copolymer obtained. The following initiators can be used in particular:

[0142] - peroxides, such as hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyoctanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxyisobutyrate, lauroyl peroxide, tert-amyl peroxypivalate, tert-butyl peroxypivalate, dicumyl peroxide, benzoyl peroxide, sodium persulfate, potassium persulfate or ammonium persulfate,

[0143] - Azo compounds, such as: 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-butyronitrile), 4,4'-azobis(4-pentanoic acid), 1,1'-azobis(cyclohexanecarbonitrile), 2-(tert-butylazo)-2-cyanopropane, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[2-methyl-N-(hydroxyethyl)propionamide], 2,2'-azobis(N,N'-dimethyleneisobutylamidine) dihydrochloride, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutyramide), 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)ethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] or 2,2'-azobis(isobutyramide) dihydrate,

[0144] - a redox system comprising a combination, such as a mixture of hydrogen peroxide, alkyl peroxides, peresters, percarbonates, persulfates, etc. with any iron salt, trivalent titanium salt, zinc formaldehyde sulfoxylate or sodium formaldehyde sulfoxylate, and reducing sugars,

[0145] - alkali metal or ammonium persulfates, perborates or perchlorates in combination with alkali metal bisulfites (such as sodium metabisulfite) and reducing sugars, and

[0146] - Alkali metal persulfates in combination with arylphosphinic acids (such as phenylphosphonic acid and other acids of similar nature) and reducing sugars.

[0147] The polymerization temperature may in particular be between 25° C. and 95° C. The temperature may depend on the free radical source. If it is not a source of UV initiator type, it will be preferred to operate between 50° C. and 95° C., more preferably between 60° C. and 80° C. In general, the higher the temperature, the easier it is to initiate the polymerization (promote the polymerization), but the lower the molar mass of the copolymer obtained.

[0148] According to a preferred embodiment of the present invention, the polymer (P) is obtained by free radical polymerization of a monomer (AA), a monomer (AM) and a monomer (M1) in the presence of a free radical source so as to obtain a polymer comprising repeating units derived from monomer (AA), repeating units derived from monomer (AM) and repeating units derived from monomer (M1).

[0149] According to a more preferred embodiment, the polymer (P) is obtained by free radical polymerization of acrylic acid, acrylamide and vinylimidazole having formula (IIa).

[0150] The polymer (P) may also be prepared by any controlled free radical polymerization technique. Among these techniques, mention may be made of reversible addition-fragmentation chain transfer (RAFT) and macromolecular design via the interexchange of xanthates (MADIX).

[0151] The use of RAFT or MADIX controlled radical polymerization agents (hereinafter referred to as "RAFT / MADIX agents") has been disclosed, for example, WO 98 / 058974A (RHODIA CHIMIE) December 30, 1998 and WO 98 / 01478A (EIDUPONT DE NEMOURS AND COMMONWEALTH SCIENTIFIC AND INDUSTRIAL RESEARCH ORGANIZATION) January 15, 1998.

[0152] Preferably, the polymer (P) is obtained by free radical copolymerization of a mixture having the following molar ratios, based on the total amount of monomer (AA), monomer (AM) and monomer (M) selected from monomer (M1) and monomer (M2):

[0153] - Monomer (AA): 0.1% to 95%, notably 5% to 50%, preferably 20% to 40%,

[0154] - Monomer (AM): 0.1% to 90%, preferably 25% to 90%, more preferably 60% to 80%,

[0155] - Monomers (M): 0.1% to 50%, for example 1% to 30%, notably 1% to 20% and even 2% to 15%.

[0156] Therefore, polymer (P) preferably comprises:

[0157] - 0.1% to 95%, preferably 5% to 50%, more preferably 20% to 40% of repeating units derived from monomer (AA),

[0158] - 0.1% to 90%, preferably 25% to 90%, more preferably 50% to 80%, of repeating units derived from monomer (AM), and 1% to 50%, preferably 1% to 30%, more preferably 1% to 20% and even 2% to 15% of repeating units derived from monomer (M),

[0159] All the above % by mole refer to the total number of moles of repeating units of the polymer (P).

[0160] In a preferred embodiment of the present invention, the polymer (P) comprises:

[0161] - 5% to 50%, preferably 20% to 40%, of repeating units derived from monomer (AA),

[0162] - 25% to 90%, more preferably 50% to 80%, of repeating units derived from monomer (AM), and

[0163] - 1% to 50%, for example 1% to 30%, notably 1% to 20% and even 2% to 15% of repeating units derived from monomer (M),

[0164] All the above % by mole refer to the total number of moles of repeating units of the polymer (P).

[0165] Generally, the preparation of the polymer (P) may be carried out in a thermally isolated reactor to minimize heat exchange with the surroundings.

[0166] The polymer (P) can also be prepared by other means known to those skilled in the art, such as using a double-jacketed reactor equipped with an overhead mechanical stirrer and a thermostatic bath to control the reaction temperature to the desired range.

[0167] The monomers and other reagents may be charged to the reactor all at once, or they may be fed into the reactor with the aid of suitable dosing devices in order to control the polymerization kinetics.

[0168] Furthermore, the polymer (P) according to the present invention preferably has a number average molecular weight (Mn) of at least 90 kDa, for example between 90 and 5000 kDa, preferably from 850 kDa to 2000 kDa.

[0169] According to a preferred embodiment, polymer (P) is a statistical (random) copolymer with a weight average molecular weight of about 100 kDa to 10000 kDa, preferably 1000 kDa to 3000 kDa, which is obtained by free radical polymerization of a mixture of monomer (AA), monomer (AM), and monomer (M), the molar ratio of the mixture is preferably about:

[0170] -20% to 40% monomer (AA),

[0171] - 50% to 80% monomer (AM), and

[0172] - 2% to 15% monomers (M).

[0173] According to an embodiment of the present invention, polymer (P) is a block copolymer obtained by controlled radical polymerization using RAFT / MADIX agents.

[0174] As used herein, "block copolymer" refers to any controlled structure copolymer, including but not limited to true block polymers, which may be diblock, triblock or multiblock; branched block copolymers, also known as linear star polymers; comb polymers; and gradient polymers. Gradient polymers are linear polymers whose composition gradually changes along the polymer chain, possibly ranging from a random structure to a block-like structure. Each block of a block copolymer may itself be a homopolymer, a random copolymer, a random terpolymer, or a gradient polymer.

[0175] The polymer (P) may be provided in solid or dry form or in vectorized form, for example in the form of a solution or emulsion or suspension, in particular in the form of an aqueous solution. The vectorized form, for example an aqueous solution, may in particular contain 3 to 50% by weight, for example 5 to 30% by weight, of polymer (P). The aqueous solution containing the polymer (P) may in particular be a solution obtained by an aqueous phase preparation process at the end of a free radical polymerization process.

[0176] The polymer (P) can suitably be converted into the polymer (PN) in its neutralized form, thus comprising repeating units derived from the monomer (AA) in neutralized form.

[0177] The polymer (PN) can be prepared by neutralizing the acid groups of the repeating units derived from the monomer (AA) as defined above, wherein the neutralization of the acid groups is carried out with a salt containing a monovalent cation [salt (S)], preferably an alkali metal salt, or with ammonia, in a suitable solvent.

[0178] The salt (S) may be any salt capable of neutralizing an acid group. In some embodiments, the salt (S) is a lithium salt selected from the group consisting of lithium carbonate, lithium hydroxide, lithium bicarbonate, and combinations thereof, preferably lithium carbonate. In some embodiments, the lithium salt does not contain lithium hydroxide.

[0179] The solvent used in the neutralization step of the polymer (PH) can be any solvent capable of dissolving the salt (S) or ammonia and the resulting polymer (P). Preferably, the solvent is selected from at least one of aqueous solvents, such as water, NMP and alcohols (such as, for example, methanol, isopropanol and ethanol). Most preferably, the solvent is an aqueous solvent. Still more preferably, the solvent is water.

[0180] Preferably, the content of the salt (S) in the solvent ranges from 0.5 to 10 wt%, preferably from 1 to 5 wt%, based on the total weight of the solvent and the salt (S).

[0181] In some embodiments, where the salt (S) is a lithium salt, the concentration of the lithium salt in the solvent provides at least 0.25 equivalents, 0.5 equivalents, 0.8 equivalents, 1 equivalent, 1.5 equivalents, 2 equivalents, 2.5 equivalents, 3 equivalents, 4 equivalents of lithium to the acid groups. In some embodiments, the concentration of the lithium salt in the solvent provides up to 5 equivalents, preferably up to 4 equivalents of lithium to the acid groups.

[0182] According to said embodiment, polymer (P) comprises repeating units derived from a lithiated form of at least one α,β-ethylenically unsaturated carboxylic acid monomer.

[0183] The content of the polymer (P) in the neutralized solution ranges from 0.5 to 40 wt%, preferably from 2 to 30 wt%, more preferably from 4 to 20 wt%, based on the total weight of the solvent and the polymer (P).

[0184] The polymer (PN) is suitably separated from the solution as a solid after neutralization and optionally stored for later use.

[0185] In a preferred embodiment, the lithium salt of polymer (P), i.e. polymer (P-Li), is prepared by adding a certain amount of LiOH to at least partially completely neutralize an aqueous solution containing about 10 wt% of polymer (PH). The resulting solution has a pH in the range of 6.5 to 9, preferably in the range of 7 to 8, and contains about 10 wt% of polymer (P-Li).

[0186] The advantage is that the salted form of the repeating unit derived from the monomer (AA) can avoid chelation of lithium ions by free acid groups in the battery cell, which could reduce the first cycle coulombic efficiency and thus the initial capacity.

[0187] All details of the process of the invention as defined above and below in connection with the process comprising the use of polymer (P) also apply to the process wherein (PN) is used.

[0188] Electrode Active Materials (AM)

[0189] For the purposes of the present invention, the term "electrode active material" is intended to mean a compound capable of incorporating or inserting alkali metal or alkaline earth metal ions into its structure and releasing alkali metal or alkaline earth metal ions therefrom in large quantities during the charging and discharging phases of an electrochemical device. The electrode active material is preferably capable of incorporating or inserting and releasing lithium ions.

[0190] The nature of the electrode active material (AM) depends on whether the composition is used to make a negative electrode (anode) or a positive electrode (cathode).

[0191] In the case of forming a positive electrode for a lithium-ion secondary battery, the electrode active material may include a composite metal chalcogenide having the formula LiMQ2, where M is at least one metal selected from transition metals such as Co, Ni, Fe, Mn, Cr, and V, and Q is a chalcogen element such as O or S. Among these, a lithium-based composite metal oxide having the formula LiMO2, where M is the same as defined above, is preferably used. Preferred examples thereof may include LiCoO2, LiNiO2, LiNi x Co 1-x O2 (0 < x < 1) and spinel-structured LiMn2O4.

[0192] As an alternative, still in the case of forming a positive electrode for a lithium-ion secondary battery, the electrode active material may include an electroactive material based on lithiated or partially lithiated transition metal oxyanions having the formula M1M2(JO4) f E 1-f , where M1 is lithium, which may be partially replaced by another alkali metal that is less than 20% of the M1 metal; M2 is a transition metal selected from Fe, Mn, Ni, or a mixture thereof at an oxidation level of +2, which may be partially replaced by one or more additional metals that are at an oxidation level between +1 and +5 and are less than 35% (including 0) of the M2 metal; JO4 is any oxyanion, where J is P, S, V, Si, Nb, Mo, or a combination thereof; E is a fluoride anion, a hydroxide anion, or a chloride anion; and f is the mole fraction of the JO4 oxyanion, generally included between 0.75 and 1.

[0193] The M1M2(JO4) f E 1-f electroactive material is preferably phosphate-based and may have an ordered or modified olivine structure.

[0194] More preferably, in the case of forming the positive electrode, the electrode active material has the formula Li 3-x M’ y M” 2-y (JO4)3, where 0 ≤ x ≤ 3, 0 ≤ y ≤ 2, M’ and M” are the same or different metals, at least one of which is a transition metal; JO4 is preferably PO4, which may be partially replaced by another oxyanion, where J is S, V, Si, Nb, Mo, or a combination thereof. Even more preferably, the electrode active material is a phosphate-based electroactive material having the formula Li(Fe x Mn 1-x )PO4, where 0 ≤ x ≤ 1, such as lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), and lithium manganese phosphate.

[0195] As another alternative, still in the case of forming a positive electrode for a lithium-ion secondary battery, the electrode active material may include garnet-type inorganic particles Li7La3Zr2O 12 (LLZO) or doped LLZO inorganic particles having the general formula Li x La y Zr z A w O 12 , where:

[0196] - A represents one or more dopants selected from the group consisting of: Al, Ga, Nb, Fe, Nd, Pt, Ta, W, Mo, Hf, Si, Ca, Sr, Ba, Ge, and mixtures thereof; preferably selected from the group consisting of: Al, Ga, Nb, Fe, Nd, Pt, Ta, W, and mixtures thereof; more preferably selected from the group consisting of: Al, Ga, W, and mixtures thereof;

[0197] - w, x, y, and z are positive numbers, including various combinations of integers and fractions or decimals;

[0198] - 0 < y ≤ 3; preferably 2 ≤ y ≤ 3; preferably 2.5 ≤ y ≤ 3;

[0199] - 0 < z ≤ 2; preferably 1 ≤ z ≤ 2; preferably 1.5 ≤ z ≤ 2;

[0200] - 0 ≤ w ≤ 0.5; preferably 0 ≤ w ≤ 0.35; more preferably 0 ≤ w ≤ 0.25; and

[0201] - x is determined by the electrical neutrality of the garnet structure; and

[0202] - their combinations.

[0203] In the case of forming a negative electrode of a lithium-ion secondary battery, the electrode active material may preferably include a material selected from the group consisting of one or more carbon-based materials and one or more silicon-based materials.

[0204] In some embodiments, the carbon-based material may be selected from graphite (such as natural or artificial graphite), graphene, or carbon black.

[0205] These materials may be used alone or as a mixture of two or more of them.

[0206] The carbon-based material is preferably graphite.

[0207] The silicon-based compound may be one or more selected from the group consisting of chlorosilane, alkoxysilane, aminosilane, fluoroalkylsilane, silicon, silicon chloride, silicon carbide, and silicon oxide.

[0208] More specifically, the silicon-based compound may be silicon oxide or silicon carbide.

[0209] Silicon oxide may in particular comprise a compound having the formula SiO x Particles of, where 0.5≤x≤1, these particles are lithiated materials resulting in the formation of Li4SiO4 and Li2SO3, as disclosed in WO 2015 / 063979.

[0210] When present in the electrode active material, the silicon-based compound is contained in an amount ranging from 1% to 60% by weight, preferably from 5% to 30% by weight, relative to the total weight of the electroactive compound.

[0211] Composition (C) may further comprise one or more optional conductivity-imparting additives, which may be added in order to improve the conductivity of the resulting electrode made from the composition (C) of the present invention.

[0212] Conductive agents for use in batteries are known in the art.

[0213] Examples thereof may include: carbonaceous materials such as carbon black, graphite fine powder, carbon nanotubes, graphene, or fibers, or metal fine powders or fibers such as nickel or aluminum. The optional conductive agent is preferably carbon black. Carbon black is for example available under the trade name Super or Available below.

[0214] When present, the conductive agent is different from the carbon-based material described above.

[0215] The amount of the optional conductive agent is preferably 0 to 30 wt% of the total solids in the electrode forming composition. In particular, for a cathode forming composition, the optional conductive agent is typically 0 to 10 wt%, more preferably 0 to 5 wt% of the total solids in the composition.

[0216] For anode forming compositions that do not contain silicon-based electroactive compounds, the optional conductive agent is typically 0 wt % to 5 wt %, more preferably 0 wt % to 2 wt % of the total solids in the composition; while for anode forming compositions that contain silicon-based electroactive compounds, it has been found to be beneficial to introduce a larger amount of the optional conductive agent, typically 0.5 to 30 wt % of the total solids in the composition.

[0217] In step ii) of the method of the present invention, mixing the electrode active material (AM), the polymer (P) as defined above, and optionally at least one conductive agent is performed by dry blending these ingredients without adding any solvent, liquid, processing aid, etc. to the particle mixture. Dry mixing can be performed, for example, in a mill, mixer or blender (such as a V blender equipped with a high-intensity mixing rod, or other alternative equipment as further described below) until a uniform dry mixture is formed. After reading this document, those skilled in the art will recognize that the blending time can vary based on batch size, material, particle size, density, and other characteristics and still remain within the scope of this document.

[0218] In step iii) of the process of the invention, the powdered dry mixture obtained in step ii) is subjected to a mechanical compaction step to provide a self-supporting dry film.

[0219] The compaction of the dry mixture obtained in step ii) can be carried out by mechanical compaction, for example by means of a roller press or a tablet press, but can also be carried out by roller compaction, stacking or by any other technique suitable for the purpose.

[0220] The mechanical compaction step may be associated with a thermal consolidation step. The combination of applied pressure and heat treatment enables thermal consolidation at lower temperatures than thermal consolidation alone.

[0221] In one embodiment, the mechanical compaction step is performed by compression, suitably by compressing the dry mixture obtained in step ii) between two metal foils. Preferably, the mechanical compaction step is done by applying a compression pressure between 5 and 50 MPa, more preferably between 10 and 30 MPa.

[0222] The compacting step is conveniently carried out at a temperature not exceeding 200°C, preferably at a temperature below 180°C.

[0223] In step iv), the dry film obtained in step iii) is applied to a conductive substrate to form an electrode.

[0224] The sheet of substrate material may comprise a metal foil, in particular an aluminium foil.

[0225] Due to the improved adhesion of composition (C), the dry film obtained in step iii) can be applied to conductive substrates without any primer or adhesion layer.

[0226] Steps i) to iv) may be performed as a single step or as separate steps; during the performance of some embodiments, some of these steps may be functionally separated and / or combined.

[0227] The polymer (P) may conveniently be used as the sole binder in the preparation of electrodes according to the process of the present invention, or it may be used in a blend with PTFE.

[0228] According to another aspect of the present invention, therefore, there is provided a method for producing an electrode of an electrochemical cell [electrode (E1)], the method comprising:

[0229] - step I) combining polytetrafluoroethylene (PTFE) and a polymer (P) as defined above to provide a binder (B);

[0230] - step II) dry mixing at least one electrode active material (AM), a binder (B) as defined above, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode forming composition [composition (C1)];

[0231] - step III) feeding the composition (C1) obtained in step II) into a compactor to form a self-supporting dry film; and

[0232] - Step IV) applying the dry film to a conductive substrate to form the electrode.

[0233] In the context of the present invention, the term "PTFE" denotes a polymer obtained from the polymerization of tetrafluoroethylene (TFE).

[0234] However, it should be understood that the PTFE polymer may also contain small amounts of one or more comonomers, such as, but not limited to, hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(propyl vinyl ether), perfluoro-(2,2-dimethyl-1,3-dioxole), and the like, provided, however, that the latter does not significantly adversely affect the unique properties of tetrafluoroethylene homopolymers, such as thermal and chemical stability. Preferably, the amount of such comonomers does not exceed about 3% by mole, and more preferably is less than about 1% by mole; particularly preferred is a comonomer content of less than 0.5% by mole. In the event that the total comonomer content is greater than 0.5% by mole, it is preferred that the amount of perfluoro(alkyl vinyl ether) comonomer is less than about 0.5% by mole. Most preferred is a PTFE homopolymer.

[0235] The PTFE suitable for preparing the binder (B) of the present invention is in the form of a powder.

[0236] PTFE in powder form can be obtained by coagulating PTFE latex by means of cryogenic coagulation or by electrolytic coagulation with addition of electrolytes. See, for example, US 6790932. Preferred examples of electrolytes are:

[0237] - Aluminium sulfate (Al2(SO4)3), concentration 2 g / l, calculated based on the amount of water in the coagulation container,

[0238] - ammonium carbonate ((NH4)2CO3) at a concentration of 8 g / l, calculated on the basis of the amount of water in the coagulation vessel, or

[0239] - Nitric acid (HNO3), 25 ml of a 65% solution, calculated based on the amount of water in the coagulation container.

[0240] Alternatively, PTFE powder can be obtained from PTFE latex in gel form by coagulation with the above-mentioned electrolytes. These gels can be obtained according to patents US 6790932 and US 6780966.

[0241] After coagulation has taken place, the polymer is washed with demineralized water at room temperature. After coagulation and washing, the PTFE powder obtained therein is then dried.

[0242] PTFE in powder form typically has a particle size between 1 and 1600 microns, preferably 100 to 800 microns, and more preferably 400-700 microns.

[0243] Typically, the weight ratio PTFE / polymer (P) will be comprised between 95 / 5 wt / wt and 5 / 95 wt / wt. A person skilled in the art will choose the most appropriate weight ratio taking into account the targeted final properties of the binder (B).

[0244] In particular, when the binder (B) is used to prepare a negative electrode, the weight ratio of PTFE / polymer (P) is suitably included in the range of 50 / 50 wt / wt to 5 / 95 wt / wt.

[0245] In a preferred embodiment, the weight ratio of PTFE / polymer (P) in the binder (B) used to prepare the negative electrode is 20 / 80 wt / wt, which provides a negative electrode imparting unexpectedly improved capacity.

[0246] The applicant has surprisingly found that the amount of polymer (P) added to the PTFE does not affect the ability to fibrillate the PTFE.

[0247] The amount of binder (B) that can be used in composition (C1) is affected by various factors. One such factor is the surface area and amount of active material and the surface area and amount of any conductivity-imparting additives added to the electrode-forming composition. These factors are believed to be important because the binder particles provide a bridge between the conductor particles and the conductive material particles, which keeps them in contact.

[0248] The composition (C1 ) comprises one or more electrode active materials (AM) as defined above.

[0249] The dry mixing step II) involves fibrillation of the binder particles to produce fibrils that ultimately form a matrix for supporting the resulting material composition. The resulting dough-like material can be calendered multiple times to produce a conductive film with a desired thickness and density. Mixing can be provided by subjecting the mixture to an extruder.

[0250] The same details provided above with respect to steps i) to iv) apply to steps I) to IV), respectively.

[0251] Steps I) to IV) may be performed as a single step or as separate steps; during the execution of some embodiments, some of these steps may be functionally separated and / or combined.

[0252] The composition (C) or composition (C1) obtained in step ii) or in step II) of the process according to the invention may further comprise at least one sulfide-based solid electrolyte.

[0253] When composition (C) or composition (C1) used in the process according to the invention comprises at least one sulfide-based solid electrolyte or at least one solid electrolyte based on garnet-type inorganic particles, the present invention provides an electrode suitable for use in a solid-state battery obtainable by the process as defined above [electrode (ESS)].

[0254] Therefore, in one embodiment, the present invention provides a method for manufacturing an electrode of a solid-state battery [electrode (ESS)], the method comprising:

[0255] -a) providing a polymer (P) as defined above;

[0256] -b) dry mixing at least one electrode active material (AM), the polymer (P) provided in step i) as defined above, at least one sulfide-based solid electrolyte or at least one garnet-type inorganic particle-based solid electrolyte, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode-forming composition [composition (C')];

[0257] -c) feeding the composition (C') obtained in step ii) to a compactor to form a self-supporting dry film; and

[0258] -d) applying the dry film to a conductive substrate to form the electrode.

[0259] The same details provided above with respect to steps i) to iv) apply to steps a) to d) respectively.

[0260] In another embodiment, the present invention provides a method for manufacturing an electrode for a solid-state battery [electrode (ESS-1)], the method comprising:

[0261] - step I') combining polytetrafluoroethylene (PTFE) and a polymer (P) as defined above to provide a binder (B);

[0262] - step II') dry mixing at least one electrode active material (AM), a binder (B) as defined above, at least one sulfide-based solid electrolyte, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode-forming composition [composition (C1')];

[0263] - step III') feeding the composition (C1') obtained in step ii) to a compactor to form a self-supporting dry film; and

[0264] - Step IV') applying the dry film to a conductive substrate to form the electrode.

[0265] The same details provided above with respect to steps i) to iv) apply to steps I') to IV') respectively.

[0266] As used herein, the phrase "sulfide-based solid electrolyte" refers to a solid electrolyte that conducts Li + An inorganic solid state material that is ionic but essentially electronically insulating.

[0267] In the present invention, the term "sulfide-based solid ion-conductive inorganic particle" is not particularly limited as long as it is a solid electrolyte material containing one or more sulfur atoms in the molecular structure or composition.

[0268] The sulfide-based solid ion-conductive inorganic particles preferably contain Li, S, and an element of Groups 13 to 15 (e.g., P, Si, Sn, Ge, Al, As, Sb, or B) to increase Li ion conductivity.

[0269] The sulfide-based solid ion-conducting inorganic particles according to the present invention are preferably selected from the group consisting of:

[0270] - Lithium tin phosphide ("LSPS") materials, such as Li 10 SnP2S 12 ;

[0271] - Lithium phosphorus sulfide ("LPS") materials, such as those having the formula (Li2S) x -(P2S5) y Those glasses, crystals or glass ceramics, wherein x+y=1 and 0≤x≤1; Li7P3S 11 ;Li7PS6;Li4P2S6;Li 9.6 P3S 12 and Li3PS4;

[0272] - doped LPS, such as Li2CuPS4; Li 1+2x Zn 1-x PS4, where 0≤x≤1; Li 3.33 Mg 0.33 P2S6; and Li 4- 3x Sc x P2S6, where 0≤x≤1;

[0273] -With formula Li x P y S z O w Lithium phosphorus sulfide oxygen ("LPSO") material, wherein 0.33≤x≤0.67, 0.07≤y≤0.2, 0.4≤z≤0.55;

[0274] - Lithium phosphide materials containing X ("LXPS"), wherein X is Si, Ge, Sn, As, or Al, such as Li 10 SnP2S 12 , Li 10 GeP2S 12 , Li 10 SiP2S 12 , and Li2S-P2S5-SnS;

[0275] - lithium phosphorus oxysulfide containing X ("LXPSO"), wherein X is Si, Ge, Sn, As or Al;

[0276] -Lithium silicon sulfide ("LSS") materials, such as Li2SiS3, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , and Li2S-SiS2-Al2S3;

[0277] -Lithium boron sulfide materials, such as Li3BS3 and Li2S-B2S3-LiI;

[0278] -Lithium tin sulfide materials and lithium arsenide materials, such as Li 0.8 Sn 0.8 S2, Li4SnS4, Li 3.833 Sn 0.833 As 0.166 S4, Li3AsS4-Li4SnS4, and Ge-substituted Li3AsS4;

[0279] -Has the general formula Li a PS b X c A lithium phosphorus sulfide material, wherein X represents at least one halogen element selected from the group consisting of Cl, Br and I or a combination thereof; and a represents a number from 2.0 to 7.0, b represents a number from 3.5 to 6.0, and c represents a number from 0 to 3.0, such as Li4PS4Cl 、 Li7P2S8Cl, and Li7P2S8I.

[0280] In a more preferred embodiment, the sulfide-based solid ion-conducting inorganic particles are of the general formula Li a PS b X c Lithium phosphide materials, more particularly Argyrodite-type sulfide materials having the formula Li6PS5X, wherein X is Cl, Br, or I.

[0281] In another preferred embodiment, the argyrodite-type sulfide material having the formula Li6PS5Y lacks sulfur and / or lithium, such as Li 6-x PS 5-x Cl 1+x (where 0≤x≤0.5), or doped with heteroatoms.

[0282] Particularly preferred sulfide solid electrolytes are LPS materials, LSPS materials, and argyrodite-type sulfide materials.

[0283] The electrode (E), electrode (E1) and electrode (ESS) of the present invention are particularly suitable for use in electrochemical devices, in particular secondary batteries.

[0284] In one aspect, the present invention provides an electrochemical device that is a secondary battery, comprising:

[0285] - positive and negative electrodes,

[0286] At least one of the positive electrode and the negative electrode is an electrode (E), (E1) or (ESS) according to the present invention.

[0287] In another object, the present invention provides a solid-state battery comprising a composite solid electrolyte membrane, a positive electrode and a negative electrode,

[0288] Wherein at least one of the negative electrode or the positive electrode is an electrode according to the present invention (ESS).

[0289] The secondary battery of the present invention is preferably an alkali metal or alkaline earth metal secondary battery.

[0290] The secondary battery of the present invention is more preferably a lithium ion secondary battery.

[0291] The electrochemical device according to the present invention can be prepared by standard methods known to those skilled in the art.

[0292] Should the disclosure of any patents, patent applications, and publications incorporated herein by reference conflict with the description of the present application to the extent that it might render a term unclear, the present invention shall take precedence.

[0293] The present invention will now be described with reference to the following examples, which are intended to be illustrative only and are not intended to limit the scope of the present invention.

[0294] Examples

[0295] Materials and methods

[0296] Silicon oxide, KSC-1064, commercially available from Shin-Etsu, has a theoretical capacity of about 2100 mAh / g;

[0297] Graphite, commercially available as GHDR 15-4 from Imerys SA;

[0298] Carbon black, commercially available as SC45 from Irrigate Corporation;

[0299] Carbon black, commercially available as SC65 from Irrigate Corporation;

[0300] PTFE: PTFE homopolymer powder having a specific gravity of 2160 measured according to ASTM D792 and a rheological pressure of 9.50 MPa measured according to ASTM D4895;

[0301] Lithium iron phosphate LFP, available from Johnson Matthey as Life Power;

[0302] Galden HT80, commercially available from Solvay Materials;

[0303] AA: acrylic acid, available from Aldrich;

[0304] AM: acrylamide monomer (50% aqueous solution), available from SNF;

[0305] VIm: vinyl imidazole monomer, available from Aldrich.

[0306] Synthesis of AA-AM-VIm terpolymer (polymer P1)

[0307] The synthesis process was carried out in a thermally isolated reactor (thermospheric flask) to minimize heat exchange with the surroundings.

[0308] The reactor was equipped with a lid comprising multiple inlets in which a small reflux system, a mechanical stirring system, a nitrogen purge line and raw material feed lines were installed.

[0309] In the first step, all monomers (117.8 g AA, 478.5 g AM, 18 g VIm), solvent (water 871.6 g) and transfer agent are loaded into a reactor and kept at room temperature for about 1 hour under stirring and nitrogen purge. Then, a redox initiator is added to the reaction mixture. A thermal initiator is also added to the reaction mixture at the same time. The initiator is homogenized in the reaction mixture for a few minutes under mechanical stirring, and then stirring and nitrogen purge are stopped.

[0310] Due to the exothermic effect, the temperature of the obtained reaction mixture increased from room temperature to about 80° C.-90° C. in about half an hour to one hour. The reaction mixture was then kept in the reaction flask for another 24 hours.

[0311] The polymer obtained had a Mw of 1400 kDa measured by GPC.

[0312] Powder preparation of polymer P1:

[0313] The powder of polymer P1 obtained as detailed above was prepared by drying the polymer solution in an oven and subsequently grinding in a mortar grinder from Retsch model RM200 according to the following procedure.

[0314] 50 g of an aqueous solution of polymer P1 (polymer content 7%) were dried in an oven at 70° C. for 12 hours to remove water. The polymer mass obtained was then ground into a fine powder by using an automatic mortar for a total time of 20 minutes.

[0315] Polymer Blending:

[0316] Powders of polymer P1 and PTFE were mixed manually in powder form in ratios of 1:1 and 4:1.

[0317] Membrane preparation

[0318] 7 g of a powder mixture of polymer P1 and PTFE were ground in an automatic stainless steel mortar for 8 minutes, with the addition of 5 mL of Galden as lubricant. The pre-film thus obtained was manually manipulated in order to fibrillate the polymer and obtain a rough and cohesive free-standing film. The film was calendered to reduce the thickness to less than 200 μm.

[0319] Lamination with metal substrates:

[0320] The film obtained as detailed above was placed between two aluminum foils and preheated in a press at 150° C. for 10 minutes. 160 bar was then applied for 10 minutes to laminate the film to the aluminum foil at a temperature of 150° C. and a pressure of 160 bar. The press was then cooled to room temperature without releasing the pressure.

[0321] The same procedure was performed using two copper foils instead of the aluminum foil.

[0322] Adhesion Assessment and Measurement

[0323] The 3-layer structure obtained after lamination (metal foil / film / metal foil) was subjected to the adhesion evaluation between the laminated sample and the foil as described above and measured according to ASTM D 1876. The adhesion levels are reported in Table 1. When the film was prepared by compression between two aluminum foils or between two copper foils using PTFE powder alone, no adhesion was observed.

[0324] The peel strength was evaluated based on the following criteria: A larger value of the peel strength indicates better intimate adhesion between the polymer and the current collector.

[0325] A: Peel strength of at least 5.0N / m

[0326] B: Peel strength of at least 0.1 N / m and less than 5.0 N / m

[0327] C: Adhesion is obtained, which is difficult to measure due to the rigidity of the specimen

[0328] D: No adhesion

[0329] Table 1

[0330]

[0331] Example 1: LFP electrode preparation composition of polymer (P1) and PTFE

[0332] A dry mixture of 6.48 g of LFP and 0.36 g of SC65 was prepared by grinding the powders in an electric mortar for 10 minutes.

[0333] 4 ml of Galden as lubricant was added to the powder mixture and the complex was mixed in an electric mortar for 1 minute. A homogeneous paste was obtained.

[0334] 0.18 g of polymer P1 powder, 0.18 g of PTFE and 3 ml of Galden as lubricant were added to the homogeneous paste and mixed in a mortar grinder for 5 min. A homogeneous composite was obtained.

[0335] The composite is then manually manipulated in order to fibrillate the polymer and obtain a rough and cohesive free-standing film.

[0336] The film was calendered to reduce the thickness to below 200 μm.

[0337] The resulting positive electrode had the following composition: 90 wt% LFP, 2.5 wt% polymer P1, 2.5 wt% PTFE and 5 wt% carbon black.

[0338] In this way, an electrode EC1 was obtained.

[0339] The EC1 sample was placed between two aluminum current collectors and preheated in a press at 150°C for 10 minutes. 160 bar was then applied for 10 minutes to laminate EC1 onto the current collectors at a temperature of 150°C and a pressure of 160 bar. The press was then cooled to room temperature without releasing the pressure.

[0340] An electrode laminated on an Al current collector was obtained.

[0341] Example 2: 1:1 polymer P1 and PTFE graphite / silicon electrode preparation composition

[0342] A dry mixture of 5.41 g of graphite, 1.36 g of silicon and 0.072 g of SC45 was prepared by grinding the powders in an electric mortar for 10 minutes.

[0343] 5 ml of Galden as lubricant was added to the powder mixture and the complex was mixed in an electric mortar for 1 minute. A homogeneous paste was obtained.

[0344] 0.18 g of polymer P1 powder, 0.18 g of PTFE and 4 ml of Galden as lubricant were added to the homogeneous paste and mixed in a mortar grinder for 5 min. A homogeneous composite was obtained.

[0345] The composite is then manually manipulated in order to fibrillate the polymer and obtain a rough and cohesive free-standing film.

[0346] The film was calendered to reduce the thickness to below 200 μm.

[0347] The resulting negative electrode had the following composition: 75.2 wt % graphite, 18.8 wt % silicon, 2.5 wt % polymer P1, 2.5 wt % PTFE and 1 wt % carbon black.

[0348] In this way, electrode EC2 was obtained.

[0349] The EC2 sample was placed between two copper current collectors and preheated in a press at 150°C for 10 minutes. 160 bar was then applied for 10 minutes to laminate the EC2 onto the current collectors at a temperature of 150°C and a pressure of 160 bar. The press was then cooled to room temperature without releasing the pressure.

[0350] An electrode laminated on a Cu current collector was obtained.

[0351] Example 3: Graphite / Silicon Electrode Preparation Composition of Polymer P1

[0352] A dry mixture of 3.82 g of graphite, 0.95 g of silicon and 0.050 g of SC45 was prepared by grinding the powders in an electric mortar for 10 minutes.

[0353] 2.38 g of polymer P1 powder were added to these powders and mixed in a mortar grinder for 5 min to obtain a homogeneous distribution.

[0354] The powder was spread between two copper current collectors and preheated in a press at 150°C for 10 minutes. 160 bar was then applied for 10 minutes to press the EC3 layer onto the current collectors at a temperature of 150°C and a pressure of 160 bar. The press was then cooled to room temperature without releasing the pressure.

[0355] An electrode laminated on a Cu current collector was obtained.

[0356] The resulting negative electrode had the following composition: 53 wt% of graphite, 13.3 wt% of silicon, 33 wt% of polymer P1 and 0.71 wt% of carbon black.

[0357] Sample EC3 was thus obtained.

[0358] Example 4: 4:1 polymer P1 and PTFE graphite / silicon electrode preparation composition

[0359] A dry mixture of 5.41 g of graphite, 1.36 g of silicon and 0.072 g of SC45 was prepared by grinding the powders in an electric mortar for 10 minutes.

[0360] 5 ml of Galden was added to the powder mixture and the complex was mixed in an electric mortar for 1 minute. A homogeneous paste was obtained.

[0361] 0.288 g of polymer (A) powder, 0.072 g of PTFE and 4 ml of Galden were added to the homogeneous paste and mixed in a mortar grinder for 5 min. A homogeneous composite was obtained.

[0362] The composite is then manually manipulated in order to fibrillate the polymer and obtain a rough and cohesive free-standing film.

[0363] The film was calendered to reduce the thickness to below 200 μm.

[0364] The resulting negative electrode had the following composition: 75.2 wt.% graphite, 18.8 wt.% silicon, 2.5 wt.% polymer (A), 2.5% PTFE, and 1 wt.% carbon black.

[0365] In this way, electrode EC4 was obtained.

[0366] The EC4 sample was placed between two copper current collectors and preheated in a press at 150°C for 10 minutes. 160 bar was then applied for 10 minutes to laminate the EC4 onto the current collectors at a temperature of 150°C and a pressure of 160 bar. The press was then cooled to room temperature without releasing the pressure.

[0367] Comparative Example 1: Preparation of LFP Electrode in PTFE Condition

[0368] A dry mixture of 6.48 g of LFP and 0.36 g of SC65 was prepared by grinding the powders in an electric mortar for 10 minutes.

[0369] 4 ml of Galden as lubricant was added to the powder mixture and the complex was mixed in an electric mortar for 1 minute. A homogeneous paste was obtained.

[0370] 0.36 g of PTFE and 3 ml of Galden as lubricant were added to the homogeneous paste and mixed in a mortar grinder for 5 min. A homogeneous composite was obtained.

[0371] The composite is then manually manipulated in order to fibrillate the polymer and obtain a rough and cohesive free-standing film.

[0372] The film was calendered to reduce the thickness to below 200 μm.

[0373] The resulting positive electrode had the following composition: 90 wt% LFP, 5% PTFE, and 5 wt% carbon black.

[0374] In this way, the electrode CE1 is obtained.

[0375] The CE1 sample was placed between two aluminum current collectors and preheated in a press at 150°C for 10 minutes. 160 bar was then applied for 10 minutes to laminate CE1 onto the current collectors at a temperature of 150°C and a pressure of 160 bar. The press was then cooled to room temperature without releasing the pressure.

[0376] No lamination of the electrodes with aluminum was obtained.

[0377] Comparative Example 2: Preparation of Graphite / Silicon Electrode in the PTFE Environment

[0378] A dry mixture of 5.41 g of graphite, 1.36 g of silicon and 0.072 g of SC45 was prepared by grinding the powders in an electric mortar for 10 minutes.

[0379] 5 ml of Galden as lubricant was added to the powder mixture and the complex was mixed in an electric mortar for 1 minute. A homogeneous paste was obtained.

[0380] 0.36 g of PTFE and 4 ml of Galden as lubricant were added to the homogeneous paste and mixed in a mortar grinder for 5 min. A homogeneous composite was obtained.

[0381] The composite is then manually manipulated in order to fibrillate the polymer and obtain a rough and cohesive free-standing film.

[0382] The film was calendered to reduce the thickness to below 200 μm.

[0383] The resulting negative electrode had the following composition: 75.2 wt % graphite, 18.8 wt % silicon, 5 wt % PTFE, and 1 wt % carbon black.

[0384] In this way, the electrode CE2 is obtained.

[0385] The CE2 sample was placed between two copper current collectors and preheated in a press at 150°C for 10 minutes. 160 bar was then applied for 10 minutes to press the CE2 layer onto the current collectors at a temperature of 150°C and a pressure of 160 bar. The press was then cooled to room temperature without releasing the pressure.

[0386] No lamination of electrodes with copper was obtained.

[0387] Adhesion of electrode compositions to current collectors: evaluation and measurement

[0388] The adhesion between the electrode composition obtained as described above and the copper or aluminum foil was evaluated and measured according to ASTM D 1876 on the 3-layer structure (metal foil / film / metal foil) obtained after lamination. The adhesion values ​​are reported in Table 2. No adhesion was observed for CE1 and CE2.

[0389] The peel strength was evaluated based on the following criteria: A larger value of the peel strength indicates better close adhesion between the negative electrode mixed material layer and the current collector.

[0390] A: Peel strength of at least 2.0N / m

[0391] B: Peel strength of at least 0.1 N / m and less than 2.0 N / m

[0392] C: Adhesion is obtained, which is difficult to measure due to the rigidity of the specimen

[0393] D: No adhesion

[0394] Table 2

[0395] Adhesion level EC1 A EC2 A EC3 C CE1 D CE2 D

[0396] Resistance measurement

[0397] The resistance of EC1, EC2, CE1 and CE2 was measured with a Keithley multimeter. A disk with a diameter of 20 mm obtained from the sample was pressed between two electrodes with a diameter of 10 mm for 1 min, which were connected to a Keithley with a dynamometer applying 50 N, and then the resistance was recorded. The average resistance of the two samples, calculated as the average of three repeated measurements, is reported in Table 3 below. The values ​​for the two compositions are similar.

[0398] Table 3

[0399] Resistance (Ω) EC1 3.2 CE1 3.2 EC2 0.2 CE2 0.2

[0400] The data show that the binders of the present invention have improved adhesion to current collectors while they maintain good conductive properties, making them suitable for use as binders for electrodes.

[0401] Cyclic voltammetry evaluation

[0402] Cyclic voltammetry was performed on EC2 and EC4 samples to evaluate different ratios of binder. Tests were performed in coin cell cells at 3 and 0.01 V lithium vs. negative electrode settings at a scan rate of 10 mV / s. 1M LiPF6 in EC:DMC 1:1 vol / vol was used as the electrolyte. Table 4 contains data on peak positions and heights for the first cycle:

[0403] Table 4

[0404]

[0405] The results show that reducing the PTFE content maintains a very good electrochemical behavior: the peak positions are not changed and the extracted current is not reduced.

Claims

1. A method for producing an electrode of an electrochemical cell [electrode (E)], the method comprising the following steps, preferably consisting of the following steps: -i) providing a polymer (P) comprising: (A) repeating units derived from at least one α,β-ethylenically unsaturated carboxylic acid monomer [monomer (AA)]; and (B) repeating units derived from at least one (meth)acrylamide monomer [monomer (AM)] having formula (I) in R 5 represents a hydrogen atom or a methyl group, R 6 and R 7 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, R 8 and R 9 , which are the same as or different from each other, may be selected from the group consisting of a hydrogen atom, a straight or branched chain alkyl group having 1 to 6 carbon atoms, a carboxyl group, and an amide group; (C) optionally, a repeating unit derived from at least one monomer (M) selected from the group consisting of monomer (M1) and monomer (M2), in - Monomer (M1) is an ethylenically unsaturated monomer carrying an unsaturated heterocyclic group having at least one nitrogen atom, said monomer (M1) having the following formula (II): in: R 1 is H or alkyl, wherein the alkyl is preferably methyl; R 2 is H or alkyl; R 3 and R 4 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms; A is a connecting bond selected from the group consisting of: - single covalent bonds; and - spacer groups; wherein X, Y and Z are independently selected from carbon atoms or nitrogen atoms; wherein a, b and c are independently selected from integers 1 to 2; Each dashed line represents an optional double bond; - a monomer (M2), which is different from monomer (AA) and monomer (AM), said monomer (M2) having the following formula (III): in: R i Selected from the group consisting of: H, -COOH, -CH2COOH or alkyl, wherein the alkyl is preferably methyl; R ii and R iii , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, or may be a -COOH group; B is a linker selected from the group consisting of: a -C(O)-O- group and a -C(O)-NH- group; R x A straight or branched C3-C4- 20 Hydrocarbon chain part: ether (-O-), heterocyclic group, sulfonic acid group (-SO3H), sulfonic acid salt (-SO3Cat), phosphonic acid group (-PO3H2), phosphonic acid salt (-PO3Cat2), phosphoric acid group (-OPO3H2), and phosphoric acid salt (-OPO3Cat2), wherein Cat is a monovalent cation, which is preferably selected from alkali metal cations, more preferably selected from Na + , K + and Li + ; -ii) dry mixing at least one electrode active material (AM), the polymer (P) provided in step i) as defined above, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode forming composition [composition (C)]; -iii) feeding the composition (C) obtained in step ii) to a compactor to form a self-supporting dry film; and -iv) applying the dry film to a conductive substrate to form the electrode.

2. The method according to claim 1, wherein: Monomer (AA) is a compound having formula (IV): Where R 4 , R 5 and R 6 , which are the same as or different from each other, are independently selected from a hydrogen atom and a C1-C3 hydrocarbon group.

3. The method according to claim 1, wherein: The monomer (AM) of formula (I) is selected from the group consisting of (meth)acrylamide or N-substituted (meth)acrylamide, such as N-alkylacrylamide, N,N-dialkylacrylamide.

4. The method according to claim 1, wherein: The monomer (M1) is selected from the group consisting of: Vinylimidazole (VIm) having the formula (IIa): 2-Methyl-1-vinylimidazole having formula (IIb) 1-vinyl-1,2,4-triazole having formula (IIc) 2-vinylpyrazine having formula (IId) 4-vinylpyridine having formula (IIe) 2-vinylpyridine having formula (IIf) Hydroxy-(meth)acrylate imidazole derivatives having formula (IIg) 5. A method according to any one of the preceding claims, wherein: The polymer (P) comprises: - 0.1% to 95%, preferably 5% to 50%, more preferably 20% to 40% of repeating units derived from monomer (AA), - 0.1% to 90%, preferably 25% to 90%, more preferably 50% to 80% of repeating units derived from monomer (AM), and - 1% to 50%, preferably 1% to 30%, more preferably 1% to 20% and even 2% to 15% of recurring units derived from monomer (M), wherein the amount of at least one of monomer (AA) and monomer (AM) is not 0%, All the above % by mole refer to the total number of moles of repeating units of the polymer (P).

6. A method according to any one of the preceding claims, wherein: The composition (C) further comprises one or more additives which impart conductivity.

7. An electrode (E) for a secondary battery, obtainable by the method according to any one of claims 1 to 6.

8. A method for producing an electrode of an electrochemical cell [electrode (E1)], the method comprising the following steps, preferably consisting of the following steps: - Step I) combining polytetrafluoroethylene (PTFE) and a polymer (P) to provide a binder (B), the polymer comprising: (A) repeating units derived from at least one α,β-ethylenically unsaturated carboxylic acid monomer [monomer (AA)]; and (B) repeating units derived from at least one (meth)acrylamide monomer [monomer (AM)] having formula (I) in R 5 represents a hydrogen atom or a methyl group, R 6 and R 7 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, R 8 and R 9 , which are the same as or different from each other, may be selected from the group consisting of a hydrogen atom, a straight or branched chain alkyl group having 1 to 6 carbon atoms, a carboxyl group, and an amide group; (C) optionally, a repeating unit derived from at least one monomer (M) selected from the group consisting of monomer (M1) and monomer (M2), in - Monomer (M1) is an ethylenically unsaturated monomer carrying an unsaturated heterocyclic group having at least one nitrogen atom, said monomer (M1) having the following formula (II): in: R 1 is H or alkyl, wherein the alkyl is preferably methyl; R 2 is H or alkyl; R 3 and R 4 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms; A is a connecting bond selected from the group consisting of: - single covalent bonds; and - spacer groups; wherein X, Y and Z are independently selected from carbon atoms or nitrogen atoms; wherein a, b and c are independently selected from integers 1 to 2; Each dashed line represents an optional double bond; - a monomer (M2), which is different from monomer (AA) and monomer (AM), said monomer (M2) having the following formula (III): in: R i Selected from the group consisting of: H, -COOH, -CH2COOH or alkyl, wherein the alkyl is preferably methyl; R ii and R iii , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, or may be a -COOH group; B is a linker selected from the group consisting of: a -C(O)-O- group and a -C(O)-NH- group; R x A straight or branched C3-C4- 20 Hydrocarbon chain part: ether (-O-), heterocyclic group, sulfonic acid group (-SO3H), sulfonic acid salt (-SO3Cat), phosphonic acid group (-PO3H2), phosphonic acid salt (-PO3Cat2), phosphoric acid group (-OPO3H2), and phosphoric acid salt (-OPO3Cat2), wherein Cat is a monovalent cation, which is preferably selected from alkali metal cations, more preferably selected from Na + , K + and Li + ; - step II) dry mixing at least one electrode active material (AM), a binder (B) as defined above, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode forming composition [composition (C1)]; - step III) feeding the composition (C1) obtained in step ii) into a compactor to form a self-supporting dry film; and - Step IV) applying the dry film to a conductive substrate to form the electrode.

9. The method according to claim 8, wherein: The weight ratio PTFE / polymer (P) in the composition (C1) is comprised between 95 / 5 wt / wt and 5 / 95 wt / wt. 10 . An electrode (E1) for a secondary battery, obtainable by the method according to claim 8 .

11. A method for manufacturing an electrode for a solid-state battery [electrode (ESS)], the method comprising the following steps, preferably consisting of the following steps: -a) providing a polymer (P) comprising: (A) repeating units derived from at least one α,β-ethylenically unsaturated carboxylic acid monomer [monomer (AA)]; and (B) repeating units derived from at least one (meth)acrylamide monomer [monomer (AM)] having formula (I) in R 5 represents a hydrogen atom or a methyl group, R 6 and R 7 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, R 8 and R 9 , which are the same as or different from each other, may be selected from the group consisting of a hydrogen atom, a straight or branched chain alkyl group having 1 to 6 carbon atoms, a carboxyl group, and an amide group; (C) optionally, a repeating unit derived from at least one monomer (M) selected from the group consisting of monomer (M1) and monomer (M2), in - Monomer (M1) is an ethylenically unsaturated monomer carrying an unsaturated heterocyclic group having at least one nitrogen atom, said monomer (M1) having the following formula (II): in: R 1 is H or alkyl, wherein the alkyl is preferably methyl; R 2 is H or alkyl; R 3 and R 4 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms; A is a connecting bond selected from the group consisting of: - single covalent bonds; and - spacer groups; wherein X, Y and Z are independently selected from carbon atoms or nitrogen atoms; wherein a, b and c are independently selected from integers 1 to 2; Each dashed line represents an optional double bond; - a monomer (M2), which is different from monomer (AA) and monomer (AM), said monomer (M2) having the following formula (III): in: R i Selected from the group consisting of: H, -COOH, -CH2COOH or alkyl, wherein the alkyl is preferably methyl; R ii and R iii , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms, or may be a -COOH group; B is a linker selected from the group consisting of: a -C(O)-O- group and a -C(O)-NH- group; R x A straight or branched C3-C4- 20 Hydrocarbon chain part: ether (-O-), heterocyclic group, sulfonic acid group (-SO3H), sulfonic acid salt (-SO3Cat), phosphonic acid group (-PO3H2), phosphonic acid salt (-PO3Cat2), phosphoric acid group (-OPO3H2), and phosphoric acid salt (-OPO3Cat2), wherein Cat is a monovalent cation, which is preferably selected from alkali metal cations, more preferably selected from Na + , K + and Li + ; -b) dry mixing at least one electrode active material (AM), the polymer (P) provided in step i) as defined above, at least one sulfide-based solid electrolyte or at least one garnet-type inorganic particle-based solid electrolyte, and optionally at least one conductive agent in the absence of a solvent to provide a dry electrode-forming composition [composition (C')]; -c) feeding the composition (C') obtained in step b) to a compactor to form a self-supporting dry film; and -d) applying the dry film to a conductive substrate to form the electrode.

12. An electrode for a secondary battery (ESS), obtainable by the method according to claim 11.

13. The method of any one of claims 1 to 6, claims 8 to 9 or claim 11, wherein: The polymer (P) is in its neutralized form (PN).

14. An electrochemical device, such as a secondary battery or a capacitor, wherein at least one of the positive electrode or the negative electrode is the electrode (E) according to claim 7, the electrode (E1) according to claim 10, or the electrode (ESS) according to claim 12.

15. A method according to any one of the preceding claims, wherein: The active material (AM) includes a material selected from the group consisting of one or more carbon-based materials and one or more silicon-based materials.

16. A method according to any one of the preceding claims, wherein: The active material (AM) is a material having the formula Li(Fe x Mn 1-x )PO4, where 0≤x≤1, such as lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP) and lithium manganese phosphate.

Citation Information

Patent Citations

  • Coagulation process of PTFE fine powders

    US6780966B2

  • Process for obtaining non thermoprocessable fine powders of homopolymer or modified PTFE

    US6790932B2

  • Polymerization with living characteristics

    WO1998001478A1

  • Method for block polymer synthesis by controlled radical polymerisation

    WO1998058974A1

  • Negative electrode active material, production method for negative electrode active material, and lithium ion secondary battery

    WO2015063979A1